Monolithically Integrated Light Feedback Control Circuit for Blue/UV LED Smart Package - Zahra Kolahdouz Esfahani; Massoud Tohidian; Henk van Zeijl; Mohammadreza Kolahdouz; Guoqi Zhang (IEEE Photonics Journal, 2017)
Given the performance decay of high-power light-emitting diode (LED) chips over time and package condition changes, having a reliable output light for sensitive applications is a point of concern. In this study, a light feedback control circuit, including blue-selective photodiodes, for blue/ultraviolet (UV) LED, has been designed and implemented using a low-cost seven-mask BiCMOS process. The feedback circuit was monolithically integrated in a package with four high-power blue LED chips. For sensing the intensity of exact colored blue/UV light in the package, selective photodiodes at 480-nm wavelength were implemented. An opamp-based feedback circuit combined with a high-power transistor controls the output light based on real-time sensor data. The whole system is a low-cost integrated package that guarantees a stable and reliable output light under different working conditions. Output light can be also controlled linearly by a reference input voltage.